Exploring the molecular profile of localized colon cancer: insights from the AIO Colopredict Plus registry - Ekmekciu, Ira; Zucha, Doreen Maria; Christmann, Jens; Wisser, Sarah; Heuer, Vera; Sargin, Buelent; Hollerbach, Stephan; Lamberti, Christof; Müller, Lothar; Lugnier, Celine; Verdoodt, Berlinda; Denz, Robin; et al. (Frontiers in Oncology, 2024)
IntroductionUnderstanding the mutational landscape of colon cancer (CC) is crucial for targeted therapy development. Microsatellite instability (MSI-H), rat sarcoma (RAS), and B-Raf proto-oncogene, serine/threonine kinase (BRAF) mutations (MT) are pivotal markers. Further investigation into clinicopathological features of RAS and BRAF MT in microsatellite stable (MSS) and MSI-H tumors is warranted.MethodsA retrospective analysis of 4883 localized CC patients (pts.) was conducted. Molecular profiling assessed MSI, KRAS, NRAS, and BRAF MT. Correlation with clinicopathological data employed ANOVA and Chi-square tests. Disease-free survival (DFS) and overall survival (OS) were analyzed adjusting for age, gender, sidedness, UICC stage, Charlson Comorbidity Index (CCI). A Cox model incorporated all variables as covariates.ResultsThis analysis included 4883 pts. (2302 female/2572 male, 3865 (79.2%) MSS, 1018 (20.8%) MSI-H). MSS pts. had more All-Wild Type (WT), KRAS MT, and NRAS MT tumors vs. MSI-H pts. (42.1% vs. 21.1%; 39.8% vs. 15.4%; 3.6% vs. 0.7%; p<0.001 for each). BRAF MT tumors (95.5% BRAF V600E MT) were more prevalent in MSI-H individuals (62.8% vs. 8.1%, p<0.001). KRAS and BRAF MT tumors were more frequently right-sided, while BRAF MT tumors were associated with female gender, advanced disease stage, lymph node positivity, and poorer differentiation in the MSS subset (p<0.001). Common KRAS mutations included p.G12D (30.44%) and p.G12V (21.3%) in MSS and p.G13D (28.9%) and p.G12D (22.37%) in MSI-H. NRAS MT tumors were dominated by codon 61 mutations (51.7%). Survival analysis revealed worst prognosis in BRAF MT MSS tumors (DFS: HR 1.74 (95% CI 1.15-2.62, p=0.009; OS: HR 1.61 (95% CI 0.99-2.6), p=0.055). The 3-years DFS and 5-years OS rates were lowest in this subset (61.6% and 57.7% respectively).DiscussionThese findings highlight the complex interplay between molecular subtypes, clinicopathological features, and survival outcomes in early CC. Further research is needed to elucidate underlying mechanisms and develop personalized treatment strategies.